Comparing the Predictive Power of Subjective and Objective Health Indicators: Changes in Hand Grip Strength and Overall Satisfaction with Life as Predictors of Mortality - Jens Ambrasat; Jürgen Schupp; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Self-reported measures of health are generally treated as weak measures of respondents' objective health status. On the other hand, most surveys use self-reported health to measure health status and to determine the effects of a range of other socio-economic characteristics of the local environment on individual health. It is therefore of interest to the public health research community to verify the validity of self-reported health data. We do this by analyzing data from a longitudinal household panel survey: the German Socio-Economic Panel Study (SOEP). In 2006, and again in 2008, hand grip strength was measured as part of the SOEP. The hand grip data can be compared with other indicators of health and well-being from the SOEP survey. In a first step, we examine short-term mortality outcomes predicted by changes in hand grip strength. Then we compare the predictive power of the results with those of a subjective indicator of well-being: overall life satisfaction. We find that both measures are related to mortality risk. However, the effects are quite independent. Thus we argue that changes in hand grip strength and overall life satisfaction capture two different aspects of health status and its changes. We therefore test this hypothesis by correlating the indicators with other survey-based health measures that were also taken in the SOEP in 2006 and 2008.
Keywords: C81; I12; J14; 330; grip strength; subjective health status measures; mortality; subjective well-being; SOEP; Gesundheit; Befragung; Zufriedenheit; Lebensqualität; Deutschland